Design and Analysis of Microfluidic Optical Fiber Device for Refractive Index Sensing - Lim, Jun Long (2016)
In this letter, the microfluidic optical fiber devices composed of microchannel are modeled and thoroughly analyzed. The microchannel intersecting the fiber core allows direct infusion of surrounding substances for detection. The simulation results suggest that the dimension of the microchannel can significantly affect the detection sensitivity of the device. In addition, the off-center position of the microchannel also plays an important role in shaping the device performance. The optimized microfluidic device can be used for sensitive refractive index sensing and biosensing applications.